PENDAMPINGAN PENGELOLAAN UNIT USAHA HIDROPONIK PADA BUMDes POSI-POSI DI DESA GUAEMADU KABUPATEN HALMAHERA BARAT - Abdullah W Jabid; Suratno Amiro; Fajri Hatim (Pusat Riset dan Inovasi Nasional, 2022)
This community service activity aims to further socialize hydroponic plant activities, especially in areas where the soil is not suitable for conventional plants, such as Guaemadu Village, South Jailolo District, West Halmahera Regency. Hydroponic cultivation is very suitable to be applied in this village which is already crowded by settlements and buildings and soil conditions are in the mountains or the land is not fertile. Limited agricultural land, making people have to find food supplies from outside the area. This can certainly be an attractive business opportunity and can increase family income. Hydroponic cultivation can also be developed into a home industry business or SMEs (small and micro businesses). With hydroponics can also create a beautiful and green environment, while still being able to maintain a clean and healthy environment